2017
DOI: 10.1016/j.ijpharm.2017.04.082
|View full text |Cite
|
Sign up to set email alerts
|

Cubosomes post-loaded with antimicrobial peptides: characterization, bactericidal effect and proteolytic stability

Abstract: Novel antibiotics, such as antimicrobial peptides (AMPs), have recently attended more and more attraction. In this work, dispersed cubic liquid crystalline gel (cubosomes) was used as drug delivery vehicles for three AMPs (AP114, DPK-060 and LL-37). Association of peptides onto cubosomes was studied at two cubosome/peptide ratios using high performance liquid chromatography, ζ-potential and circular dichroism measurements. AMPs impact on the cubosome structure was investigated using small angle x-ray scatterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 38 publications
3
57
0
Order By: Relevance
“…The formation of cubosomes/hexosomes, similar to microemulsions, is followed by titrating the precursor liquid with an aqueous solution until the lipids self‐assemble to form the appropriate colloidal structures. In order to stabilize these colloidal mesophase systems, the block copolymers, such as Pluronic F 127, Poloxamer 707, and Koliphor P 407, are used (Boge et al., 2017; Meikle et al., 2017).…”
Section: Role Of the Nanocarriers In Improving Nutraceutical Bioavailmentioning
confidence: 99%
“…The formation of cubosomes/hexosomes, similar to microemulsions, is followed by titrating the precursor liquid with an aqueous solution until the lipids self‐assemble to form the appropriate colloidal structures. In order to stabilize these colloidal mesophase systems, the block copolymers, such as Pluronic F 127, Poloxamer 707, and Koliphor P 407, are used (Boge et al., 2017; Meikle et al., 2017).…”
Section: Role Of the Nanocarriers In Improving Nutraceutical Bioavailmentioning
confidence: 99%
“…Dispersions of these inverse (oil-continuous) structures in excess water that form cubosomes, hexosomes, and related dispersed systems provide attractive drug and functional food nanocarriers owing to their capability to solubilize not only hydrophobic but also hydrophilic and amphiphilic bioactive molecules [52e58]. The encapsulation of degradation-sensitive molecules such as PUFAs, proteins, and peptides into these structures can protect them from degradation in the biological milieu, which may be crucial for facilitating their transport through the low-pH and protease-rich gastric fluid into the small intestine for absorption [55,59]. The solution conditions such as pH and ionic strength, that are significantly changing during digestion, are important to be taken into account as they affect the intermolecular forces and thereby modify the dynamic self-assembled structural features [47,53,60,61].…”
Section: Self-assembly Of Lipid Digestion Products-the Phase Diagram mentioning
confidence: 99%
“…Boge et al demonstrated that the high affinity of AMPs to nanoparticles may retard their release, resulting in decreased amounts of free peptide available to exert their antibacterial activity. 34 Indeed, if the drug is presented to bacteria in small quantities over a prolonged period, it may be more effectively neutralized by the microorganisms than if the same quantity is delivered all at once. Thus, the high affinity of the AMPs for nanovectors and prolonged release could result in the loss of antibacterial activity.…”
Section: Release Studymentioning
confidence: 99%